Implications of accelerated agricultural growth on household incomes and poverty in Ethiopia - Dorosh, Paul A.; Thurlow, James (International Food Policy Research Institute, 2009)
This paper provides details of the analysis done for Ethiopia’s background study for its implementation of the Comprehensive Africa Agriculture Development Programme (CAADP). The analysis provides an assessment of agricultural growth options utilizing a new computable general equilibrium (CGE) model for Ethiopia based on data from the EDRI 2004/05 Ethiopia Social Accounting Matrix (SAM). The CGE model results indicate that if Ethiopia can meet its targets for crop yields and livestock productivity, then it should be possible to reach and sustain the six percent agricultural growth target during 2006-2015.